Adaptive control of a seismically excited flexible structure using active mass damping - Rabuya, Isabelo A. (2004)
A way of suppressing vibration in a flexible structure is to carry out vibration cancellation using an active mass damper (AMD). Mounted on top of the structure, the AMD generates vibration for cancellation through a controller. In this study, the controller is an adaptive filter and vibration is characterized using acceleration. The adaptive filter input is the acceleration at the base of the structure; its output drives the AMD. The least-mean-squares (LMS) algorithm is used to update the filter coefficients for adaptation. Because of the presence of the AMD, a modified LMS algorithm called the Filtered-X LMS is used in the implementation of the system. The system is realized in a feedforward control scheme, and simulated in MATLAB and Simulink using models of the flexible stucture and the cancellation path. Simulation is used to tune the step-size parameter of the adaptive filter and to make the filter learn the dynamics of the system. Pre-learned filter coefficients are used to achieve maximum cancellation in tests employing short-duration seismic events. Real-time control of the actual single-story flexible structure mounted on a shaker table is achieved through Simulink aided with additional real-time software. Results reveal that the FXLMS implementation exhibits instability at excitation frequencies near the resonant frequency of the structure. Inserting a compensation filter in the error path solves the problem, and produces a system called Filtered-E LMS. With a feedforward FELMS implementation, the reduction in top floor peak absolute acceleration with a scaled El Centro earthquake record as disturbance input is 56.5%. The study also investigates an approximation of the adaptive feedforward system using output feedback only. The adaptive feedback scheme simplifies the system by eleiminating the need for measuring the input disturbance; it performs poorly however in comparison with the adaptive feedforward system.